2019
DOI: 10.1016/j.asmr.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Effects of Limited Lateral Retinacular and Capsular Release on Lateral Patellar Translation at Various Flexion Angles in Cadaveric Specimens

Abstract: Purpose: To determine the biomechanical effect of limited lateral retinacular and capsular release on lateral patellar translation as a function of constant force at various knee flexion angles. Methods: Six pairs of bilateral cadaveric knee specimens (12 knees) were obtained from a tissue bank, dissected, and potted in a perfect lateral position based on fluoroscopy. A direct lateral force was applied to the patella through an eye screw in the midpoint of the lateral patella, and each knee underwent testing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Additionally, a competent lateral retinaculum has been confirmed in biomechanical studies to prevent lateral patellar instability. 11 Besides patellar instability, LRL would be indicated for patellofemoral pain secondary to lateral patellar hypercompression syndrome that is refractory to conservative treatment. 5 Although LRR can also be performed without a formal arthrotomy of the joint by keeping the synovial layer intact and cutting the capsular layer, LRL as an alternative offers several advantages (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a competent lateral retinaculum has been confirmed in biomechanical studies to prevent lateral patellar instability. 11 Besides patellar instability, LRL would be indicated for patellofemoral pain secondary to lateral patellar hypercompression syndrome that is refractory to conservative treatment. 5 Although LRR can also be performed without a formal arthrotomy of the joint by keeping the synovial layer intact and cutting the capsular layer, LRL as an alternative offers several advantages (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, biomechanical studies have demonstrated the importance of the lateral retinacular structures in preventing increases in medial and lateral patellar translation and alterations of patellar tracking. [8][9][10][11] Because of the importance of the lateral retinaculum, we do not recommend performing lateral release procedures and instead suggest performing lateral lengthenings to preserve the overall integrity of the lateral structures. [12][13][14] As described in this technique, it may be difficult to perform a lateral lengthening because of either poor tissue quality or the significant extent to which a lengthening would need to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…After all the arthroscopic procedures, percutaneous lateral retinacular release was performed in all patients to prevent arthritic change by reducing the patellofemoral joint pressure [ 12 ]. This release procedure was performed as previously described by Randal et al [ 13 ].…”
Section: Methodsmentioning
confidence: 99%